COMPARATIVE ANALYSIS OF INDONESIA CAPITAL MARKET REACTION BEFORE AND AFTER ANNOUNCEMENT OF PRESIDENTIAL ELECTIONS UNITED STATES 2016 DONALD TRUMP (Event Studies On Shares Member Index LQ-45) - Gunawan Jamaludin; Sri Mulyati; Trisandi Eka Putri (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2018)
This study aims to determine the empirical evidence of differences before and after the announcement of the results of the election of President of the United States 2016 Donald Trump against the average abnormal return, trading volume trading activities, and frequency trading activities of shares in the capital market in Indonesia. This study is an event study with a 15-day window event that begins on October 31 2016 (t-7) to November 18, 2016 (t+7) and the date of the announcement of the 2016 Presidential Election of the United States of America which falls on November 9, 2016 as (t0). The sample used in this research is 24 stock members of LQ-45 index chosen by purposive sampling method. The data used in this study is secondary data sourced from the website of Indonesia Stock Exchange (http://www.idx.co.id/). Expected return in this study using market model. Then the data is analyzed using Microsoft Excel 2010 and SPSS 22 applications. The result of the research shows that based on the result of paired-samples t-test it can be concluded that statistically the average difference of abnormal return variable before and after announcement of election result of President of United States 2016 Donald Trump, then based on result of wilcoxon signed rank test can be concluded that statistically the average difference of trading volume activity volume variables, and the frequency of trading activity of stock before and after the announcement of the result of the election of President of the United States 2016 Donald Trump.